Upon this rock [videorecording] - Dault, Gary Michael; Garwood, Joseph J.; McGreevy, John.; Puncher, Jennifer; Ustinou, Peter Sir.; John McGreevy Productions limited; Multimedia Entertainment (New York Multimedia Entertainment, 1993)
A tour in the Vatican's inner sanctums, secret archives, Vatican grottos, coloseum in the days of the Roman empire and Constantinople now Istanbul, a mysterious Eastern outpost of Christianity. A reenacted interviews with Emperor Constantine and Pope Gregory the Great.
Documentary.
VHS.
Editor, Christopher Sumpton.
Paolo Bonacelli as Constantine the Great ; Carlo Croccolo as Pope Gregory I.
Keywords: Church buildings -- Vatican City; Archives -- Vatican City; Catholic church -- Government -- History; Emperors -- Rome; Popes -- Vatican City; Vatican Palace (Vatican City).; Istanbul (Turkey) -- History